1966
DOI: 10.1126/science.152.3730.1756
|View full text |Cite
|
Sign up to set email alerts
|

Actin: Volume Change on Transformation of G-Form to F-Form

Abstract: The volume change occurring on polymerizing actin was measured by dilatometry. A large positive value of + 391 ml/mole was obtained for the volume change during the transformation of G- to F-actin. This large increase in volume could be interpreted as arising from the local change in the ordered water structure on the protein's surface at polymerizing sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

1967
1967
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 9 publications
3
19
1
Order By: Relevance
“…Even though electron microscopy on mitotic spindles has not been carried out on cells fixed during the application of hydrostatic pressure, light microscope studies (Pease, 1941;Zimmerman and Marsland, 1964) have demonstrated that the mitotic apparatus solates under pressure so that it is probable that the microtubules in the mitotic spindle act as those in Actinosphaerium and depolymerize when the pressure is increased. Similar results have been observed on globular to filamentous transformation in F actin (Ikkai et al, 1966), tobacco mosaic virus protein polymerization (Lauffer, 1962), and in aggregation of protein and crystal formation in sickle cell anemia (Murayama, 1966). In all these cases as well as microtubule formation, polymerization appears to be an endothermic reaction involving an increase in volume.…”
Section: Similarities In the Assembly And Disassemblysupporting
confidence: 81%
“…Even though electron microscopy on mitotic spindles has not been carried out on cells fixed during the application of hydrostatic pressure, light microscope studies (Pease, 1941;Zimmerman and Marsland, 1964) have demonstrated that the mitotic apparatus solates under pressure so that it is probable that the microtubules in the mitotic spindle act as those in Actinosphaerium and depolymerize when the pressure is increased. Similar results have been observed on globular to filamentous transformation in F actin (Ikkai et al, 1966), tobacco mosaic virus protein polymerization (Lauffer, 1962), and in aggregation of protein and crystal formation in sickle cell anemia (Murayama, 1966). In all these cases as well as microtubule formation, polymerization appears to be an endothermic reaction involving an increase in volume.…”
Section: Similarities In the Assembly And Disassemblysupporting
confidence: 81%
“…17,18 Here the utility of pressure is assured by a substantial positive change in the partial molar volume of the denatured protein upon forming protofibrils, which gives a thermodynamic driving force for dissociation at high pressure against the thermodynamic driving force for association by molecular interactions. The disulfide-deficient hen lysozyme offers a particularly simple model system for thermodynamic and kinetic studies of protofibril formation.…”
Section: Pressure Perturbation Offers a New Dimension For The Study Omentioning
confidence: 99%
“…The partial molar volume of proteins is a characteristic parameter that has been used to elucidate several processes such as the protein conformation changes, protein aggregation or polymerization [1][2][3][4][5][6]. Because of the structure complexities of proteins, it is extremely difficult to investigate thermodynamic properties directly.…”
Section: Introductionmentioning
confidence: 99%